Analisis Kesalahan Morfologi Dalam Insya - R.A Putri Rahmawati; Novita Rahmi (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2020)
This study aimed to analyze the forms of students' writing language errors in learning Arabic. The research method used qualitative research. The study was conducted at Islamic Junior High School Darul A'mal Metro. Research respondents were 30 students of grade VIII. Data collection methods were interviews and observations. The interview method was used to find out the difficulties of Arabic learning in the writing aspect. The method of observation was used to see the directly learning process in Arabic learning activities. This study used qualitative data analysis techniques, namely content analysis of morphological errors encountered in insya' text resulting from student work. The results showed that writing errors were found in the form of morphological errors. Writing mistakes in the morphological included writing errors on mudzakar and muannas words, writing errors on madhi and mudhare fi'il. This morphological error occurs due to factors that include the lack of exercise and teachers' optimization in learning could cause students' understanding of Arabic rules were less.